Nutrient stocks of Japanese blue oak (Quercus glauca Thunb.) stands on different soil parent materials. Issue 4 (1st October 2020) - Baek, Gyeongwon; Bae, Eun Ji; Kim, Choonsig
Abstract: Soil parent materials originating from different geologic settings represented broad differences in the forest nutrient environment, but few studies have been conducted on the relationships between soil parent materials and nutrient stocks in forest stands. This study was performed to compare the nutrient stocks of Japanese blue oak ( Quercus glauca Thunb.) stands grown on forest soils inherited from two different parent materials, basalt and sandstone, in southern Korea. A total of 29 Japanese blue oak trees were destructively sampled (15 trees on basalt and 14 trees on sandstone) to compare the nutrient content of the tree components (stem wood, stem bark, branches, and leaves). Samples of the forest floor and a soil depth of 0–30 cm were collected to measure the nutrient stocks of the two parent materials. The mean nutrient concentrations of the tree components varied significantly between the basalt and sandstone parent materials. The mean carbon and potassium concentrations of stem wood were significantly higher in sandstone than in basalt, whereas the nitrogen concentration of stem wood and stem bark were lower in sandstone than in basalt ( p < .05). A significantly higher carbon, nitrogen, potassium, and magnesium stocks of the forest floor were found in sandstone than in basalt. However, the soil carbon, nitrogen, calcium, and magnesium stocks at a depth of 0–30 cm were significantly higher in basalt than in sandstone. The results demonstrate that the aboveground nutrient concentration and belowground nutrient stocks of Japanese blue oak stands can be altered greatly by different parent materials.